1992
DOI: 10.1136/bmj.305.6845.79
|View full text |Cite
|
Sign up to set email alerts
|

Paralytic poliomyelitis in England and Wales, 1985-91.

Abstract: Objectives-To ascertain all cases of paralytic poliomyelitis in England and Wales during and to determine the source of infection in each case.Design Results-Of 54 suspected cases of poliomyelitis, 33 were excluded, leaving 21 cases, of which 13 were vaccine associated (nine recipient and four contact) cases, five were imported cases, and three were cases whose source of infection was unknown. No cases due to indigenous wild polioviruses were identified; two were imported cases due to wild viruses. One patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…Our overall estimate of 1 VAPP case per 2.9 million OPV doses distributed during 1990-1999 is similar to other published US studies and data from other industrialized countries, as is our finding that there is a substantially higher risk of VAPP in immunocompetent children following the first dose of OPV compared with subsequent doses. 10,11,33,41,42 Our estimate of 1 contact VAPP case per 13.3 million OPV doses distributed, however, is more than 50% lower than that estimated for the United States in the 1970s and 1980s, perhaps because of increasing immunization coverage during the past 2 to 3 decades. The distribution of the poliovirus serotypes that were isolated, with type 2 being the predominant type in immunodeficient cases and type 3 in immunocompetent cases, is also consistent with previous findings but is not fully understood.…”
Section: Impact Of Poliovirus Vaccine Policy Changesmentioning
confidence: 70%
“…Our overall estimate of 1 VAPP case per 2.9 million OPV doses distributed during 1990-1999 is similar to other published US studies and data from other industrialized countries, as is our finding that there is a substantially higher risk of VAPP in immunocompetent children following the first dose of OPV compared with subsequent doses. 10,11,33,41,42 Our estimate of 1 contact VAPP case per 13.3 million OPV doses distributed, however, is more than 50% lower than that estimated for the United States in the 1970s and 1980s, perhaps because of increasing immunization coverage during the past 2 to 3 decades. The distribution of the poliovirus serotypes that were isolated, with type 2 being the predominant type in immunodeficient cases and type 3 in immunocompetent cases, is also consistent with previous findings but is not fully understood.…”
Section: Impact Of Poliovirus Vaccine Policy Changesmentioning
confidence: 70%
“…Exhaustive national surveillance of all acute flaccid paralysis (AFP) cases in Iran, especially in recent years, revealed that only a few cases (six cases during 10-years of surveillance) had VAPP, mostly in association with immunodeficiency (iVAPP), have been reported as yet [Parvaneh et al, 2007;Rahimi et al, 2007a,b;Davarpanah et al, 2008;Mamishi et al, 2008;Shahmahmoodi et al, 2008Shahmahmoodi et al, , 2009, and no increased level of complications was observed in vaccinees. The risk of VAPP among recipients and/or contacts was 1 case per 745,000 to 7,142,000 used doses of OPV in different parts of the world [WHO, 1982;Nkowane et al, 1987;Joce et al, 1992;Strebel et al, 1992;Prevots et al, 1994;Andrus et al, 1995;Kohler et al, 1999;Zimmerman and Spann, 1999;SamoDlovich et al, 2007]. The rate of VAPP is higher with the first dose [Clements, 2000] and also among immunodeficient individuals (3,000-fold higher risk than that in immunocompetent individual) [Khetsuriani et al, 2003;Martín, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…However, if exposed to any wild or VDPV of increased virulence, they are at risk to develop AFP. Two healthy adult British males, aged 62 and 65 years, did develop poliomyelitis with AFP while on holiday in Morocco (Joce et al, 1992).…”
Section: Gaps In Protective Immunitymentioning
confidence: 98%